Repressive policy of Kazakhstan in the 20-30s of the 20th century - Saurykova, Zhanar S.; Zhaskairat T. Yernazarov, Samat B. Kurmanalin, Raisa L. Abdrakhmanova, Akkaiyn M. Balykova (Opción, 1970)
The study aims to investigate the repressive policy of Kazakhstan in the 20-30s of the 20th century and its teaching in the course ‘modern history of Kazakhstan’ via comparative qualitative research methods. As a result, the teacher, using new pedagogical technologies in the lesson, puts the student in the position of the subject of their training, and as a result, they form new knowledge, they master new ways of action. In conclusion, the tactics of the repression against the peasantry differed significantly from the repressions against other segments of society